Financing of Small and Medium-Scale Enterprises (SMEs) and Economic Growth in Nigeria - Soyemi, Kenny Adedapo; Olowofela, Olusola Enitan; Ariyibi, Mayowa Ebenezer (Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an (UNSIQ) Wonosobo, 2024)
The financing of small and medium-scale enterprises (SMEs) is a crucial aspect of economic development in Nigeria. However, SMEs often face significant challenges in accessing finance, hindering their growth and potential contributions to the economy. This study examines the role of deposit money banks in supporting SME financing in Nigeria using Central Bank of Nigeria (CBN) statistical bulletin and National Bureau of Statistics fact book (NBS) covering the period of 1990 – 2022 on yearly basis with E-view. The study found out that bank credit to small and medium scale enterprises, credit to private sector, lending rate, interest rate have positive and significant effect on gross domestic product. This study recommend that bank should enhance financial inclusion, simplify loan application processes, develop risk mitigation mechanisms, strengthen financial literacy and advisory services, foster collaboration in other to provide financing opportunities to small and medium-scale enterprises